Resolution of sclerotic lesions of dysosteosclerosis due to biallelic SLC29A3 variant in a Turkish girl. - Uludağ Alkaya, Dilek; Akpınar, Evren; Bilguvar, Kaya; Tuysuz, Beyhan (Am J Med Genet A, 2021)
Dysosteosclerosis is a group of sclerosing bone dysplasia characterized by short stature, increased bone fragility, osteosclerosis, and platyspondyly. It is a genetically heterogeneous disorder caused by biallelic mutations in the SLC29A3, TNFRSF11A, TCIRG1, and CSF1R genes. To date, four dysosteosclerosis patients with SLC29A3 mutations have been reported. Here, we report biallelic SLC29A3 (c.303_320dupCTACTTTGAGAGCTACCT) variant in a three-year-old girl. She had large anterior fontanelle, fracture history, short stature, camptodactyly, elbow contracture, and melanocytic nevus. Initial skeletal radiographs revealed platyspondyly, dense vertebral endplates (sandwich appearance of the vertebral bodies), diffuse sclerosis of the peripheral side of the pelvic bones, sclerosis of metaphysis and diaphysis of the long bones, metaphyseal widening, and diaphyseal cortical thickening. Mild sclerosis was also present in the skull base, maxilla, rib, scapula, and phalanges. Notably, we observed that sandwich vertebrae appearance significantly resolved and sclerosis of ribs, scapula, pelvis, and long bone metaphysis regressed over a 2.5-year period. However, platyspondyly, metaphyseal widening, and diaphyseal cortical thickening persisted. In conclusion, this study demonstrates spontaneous resolution of osteosclerosis, which was not described previously in patients with dysosteosclerosis.